SAB80C166 microcontroller-based inverter for three-phase induction motor drive / Syarimin Sahari - Sahari, Syarimin (2003)
This project presents a simple constant volt per hertz control, six-step output voltage for a three-phase induction motor drive. Essentially, an open loop speed control scheme is adopted. The constant V / f speed control involves simultaneous adjustment of terminal voltage and supply frequency in order to achieve variable speed with constant torque. The present project used a Siemens SAB 80C166 microcontroller to implement variable control parameter.